2016
DOI: 10.4103/0970-9185.182105
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus midazolam as adjuvants to intrathecal bupivacaine: A clinical comparison

Abstract: Background and Aims:Trials are being carried out to identify an adjuvant to intrathecal bupivacaine that preferably potentiates postoperative analgesia. This prospective, randomized, double-blind study was aimed to compare the onset and duration of sensory and motor block, postoperative analgesia and adverse effects of dexmedetomidine or midazolam given with 0.5% hyperbaric bupivacaine for spinal anesthesia.Material and Methods:A total of 80 patients, scheduled for vaginal hysterectomies, were randomly allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
3
10
0
1
Order By: Relevance
“…The results indicated that the combined administration of Dex and sufentanil as adjuvants to local anesthetic displayed an improved analgesic effect compared with the use of either drug alone. Both 0.5 µg/ml Dex and 0.5 µg/ml sufentanil have been used as adjuvants in clinical practice (12,27). In the present study, the combination of 0.25 µg/ml Dex + 0.25 µg/ml sufentanil + 0.1% ropivacaine was administered via an epidural for labor analgesia, and the efficiency and safety of the combined treatment was compared with 0.1% ropivacaine + 0.5 µg/ml Dex or 0.5 µg/ml sufentanil.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the combined administration of Dex and sufentanil as adjuvants to local anesthetic displayed an improved analgesic effect compared with the use of either drug alone. Both 0.5 µg/ml Dex and 0.5 µg/ml sufentanil have been used as adjuvants in clinical practice (12,27). In the present study, the combination of 0.25 µg/ml Dex + 0.25 µg/ml sufentanil + 0.1% ropivacaine was administered via an epidural for labor analgesia, and the efficiency and safety of the combined treatment was compared with 0.1% ropivacaine + 0.5 µg/ml Dex or 0.5 µg/ml sufentanil.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] Recently, many studies have demonstrated that intrathecal ropivacaine or bupivacaine-dexmedetomidine may increase the duration and efficacy of analgesia and decrease postoperative analgesic use, without notable adverse effects. 11,12,36) The use of dexmedetomidine as an adjuvant to bupivacaine for covering Cesarean delivery provided better intra-operative analgesia and did not affect Apgar scores or caused any noticeable side effects. 13,28) The intrathecal doses of dexmedetomidine used in our study were based on previous human studies wherein no neurotoxic effects were documented at these doses.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Forty patients undergoing vaginal hysterectomies received intrathecal administration of 3 mL of 0.5% hyperbaric bupivacaine with 5 μg dexmedetomidine in 0.5 mL of normal saline, exhibited a significantly longer duration of sensory block, and reduced doses of postoperative analgesic agents with comparable side effects when compared to the intrathecal administration of 3 mL of 0.5% hyperbaric bupivacaine with 2 mg midazolam in 0.4 mL and 0.1 mL normal saline. 46 Adding 1 μg/kg dexmedetomidine to 0.75% ropivacaine in 35 patients undergoing arthroscopic shoulder surgery with ultrasound-guided single-dose interscalene block prolonged the interscalene block, and provided better postoperative pain control during the first 24 h, compared to that produced by clonidine. 47 The addition of 2 mL of 0.5 μg/kg dexmedetomidine to 20 mL of 0.3% ropivacaine for ultrasound-guided bilateral transversus abdominis plane block for postoperative analgesia after abdominal hysterectomy surgery potentiated the analgesic properties of ropivacaine, reduced sufentanil consumption, and provided better pain control.…”
Section: Effect Of Postoperative Dexmedetomidine On Perioperative Paimentioning
confidence: 99%